Human capital as a management object in the management strategy of the region innovative development (Nexo Revista Científica, 2021)
The relevance of the problem under study is due to the fact that the role of human capital in the development of the content and dynamics of the innovation system of both a country as a whole and its individual regions is currently increasing. The purpose of the article is to develop recommendations for improving the efficiency of the use of human capital in the process of implementing innovative activities. The leading methods of studying the problem of the article include the analysis of theoretical sources, analysis of statistics, comparison. The article examines the essence of innovative development, analyses human capital and innovative development of the Odesa region, identifies problems, and elaborates ways to solve them.